Plaque Tissue Components Obtained from De Novo Lesions may Predict Restenosis after Directional Coronary Atherectomy - Arakawa, Kentaro (The Editorial Committee of Annals of Vascular Diseases, 2010)
Background: A part of coronary stenotic lesions treated with directional coronary atherectomy (DCA) occur restenosis several months later. Specimens obtained by first DCA, present the histology of culplit lesions and may predict restenosis after PCI. Methods: The study group comprised 76 patients (male/female 65/11, age 61 ± 11 years). Restenosis, defined as > 50% stenosis diameter by quantitative cineangiography, was present in 26 patients. The other 50 patients (< 50% stenosis) constitute the “no restenosis” group. Inflammatory cells and other atheroma components were planimetrically quantified as a percentage of total tissue area. Results: As regards lymphocytes, neutrophils and smooth muscle cells, the grade of amount of cells did not differ between restenosis group and no restenosis group. The amount of obtained arterial media was similar, too. However, the area occupied by macrophages or calcified fragments was significantly larger in restenosis group than no restenosis group. And there was a tendency toward larger area occupied by cholesterol gruel, thrombus and myxomatous extracellular matrix (ECM) in restenosis group. Conclusion: Rich macrophages infiltration, calcified fragments, cholesterol rich gruel and myxomatous ECM from primary lesions can be predictors of restenosis after DCA, suggesting a possible role in restenotic process after PCI.